The Survival Strategy of Indonesian Retailers in A Pandemic - Aisyah, Muniaty (Universitas Prasetiya Mulya, 2023)
Transmart, a retail business network in Indonesia, has adopted new survival strategies during the Covid-19 pandemic. This research analyzes whether the health protocol service quality and advertising affect consumers’ intention and decision to shop at Transmart during the pandemic directly and indirectly. A primary data set of 112 samples was analyzed using path analysis with the convenience sampling method. The findings show that the health protocol service quality and advertising directly affect consumers’ intention and decision to shop at Transmart during the pandemic and that consumers’ intention is an intervening variable that mediates both indirect effects.